The prevalence of serum antibodies to tick-borne infections in cattle in smallholder dairy farms in Murang'a District, Kenya; a cross-sectional study - Gitau, G.K.; Perry, Brian D.; Katende, J.M.; McDermott, John J.; Morzaria, S.P.; Young, A.S. (Elsevier, 1997)
The most important tick-borne disease of cattle in eastern, central and southern Africa is East Coast fever (ECF) caused by Theileria parva and transmitted by the tick Rhipicephalus appendiculatus. Other less-important tick-borne diseases in cattle are benign theileriosis caused by Theileria mutans, babesiosis caused by Babesia bigemina, anaplasmosis caused by Anaplasma marginale and cowdriosis caused by Cowdria ruminatum. In Murang'a District, Central Province of Kenya, five agroecological zones (AEZs) are defined according to climate, altitute and agricultural activities. A cross-sectional serological study was conducted on 750 smallholder dairy farms in Murang'a District, selected in a stratified random sampling method. The farms had a total of 362 calves. One hundred and fifty farms were studied from three administrative sublocations in each of the five AEZs. Prevalence of serum antibodies to three tick-borne parasites, that is T. parva, T. mutans and B. bigemina, were determined using the enzyme-linked inmunosorbent assay (ELISA) technique. Antibody prevalence values differed across the AEZs. The range of means for the prevalences were: T. parva (18-72 percent), T. mutans (1.5-28 percent) and B. bigemina (12-49 percent). The above results serve as indicators of the possible existence of endemic stability in some AEZs for some parasites.